Effects of Fuel Hydrochloric Acid Contamination on Selected Metals - Kaivosoja, Jonna; Sirviö, Katriina; Nuortila, Carolin; Niemi, Seppo (MDPI, 2024)
Chlorinated organic compounds, as contaminants in marine fuels, have caused severe damage, affecting both main and auxiliary engines. Contaminated fuels can cause serious damage to an engine and its components, corroding fuel pumps and blocking filters, for example. This affects the operation of the engine, and, in the most severe cases, vessel safety. This study considered fossil diesel containing hydrochloric acid as a possible product formed under certain conditions in fuel contaminated with COCs and its effects on carbon steel, stainless steel, tempering steel, and aluminum. Five fuel samples with different concentrations of hydrochloric acid were prepared, plus one sample of diesel and water. Metal bars were partially immersed in the fuel samples and stored at room temperature for approximately one month. A visual assessment found corrosion across the entire surface of all metal bars when exposed to fuel samples containing hydrochloric acid. Even the smallest acid content (25 ppm) caused corrosion, and the effects were already observable after only two days of exposure. Despite their acid contamination, the measured fuel properties fulfilled the standard for automotive fuels at the beginning of the test. The water in the diesel sample did not cause any visible corrosion.
Keywords: diesel fuel; fuel contamination; chlorinated organic compounds; hydrochloric acid; corrosion of metals; fi=Energiatekniikka|en=Energy Technology|